In vitro investigation on lactic acid bacteria isolatedfrom Yak faeces for potential probiotics - Zhang, Qingli; Wang, Meng; Ma, Xin; Li, Zhijie; Jiang, Chenghui; Pan, Yangyang; Zeng, Qiaoying (Frontiers in Cellular and Infection Microbiology, 2022)
In order to evaluate the potential and safety of lactic acid bacteria (LAB) isolated from faeces samples of Ganan yak as probiotic for prevention and/or treatment of yak diarrhea, four strains of LAB including Latilactobacillus curvatus (FY1), Weissella cibaria (FY2), Limosilactobacillus mucosae (FY3), and Lactiplantibacillus pentosus (FY4) were isolated and identified in this study. Cell surface characteristics (hydrophobicity and cell aggregation), acid resistance and bile tolerance, compatibility, antibacterial activity and in vitro cell adhesion tests were also carried out to evaluate the probiotic potential of LAB. The results showed that the four isolates had certain acid tolerance, bile salt tolerance, hydrophobicity and cell aggregation, all of which contribute to the survival and colonization of LAB in the gastrointestinal tract. There is no compatibility between the four strains, so they can be combined into a mixed probiotic formula. Antimicrobial tests showed that the four strains were antagonistic to Escherichia coli, Staphylococcus aureus, and Salmonella typhimurium. Moreover, the in vitro safety of the four isolates were determined through hemolytic analysis, gelatinase activity, and antibacterial susceptibility experiments. Theresults suggest that all the four strains were considered as safe because they had no hemolytic activity, no gelatinase activity and were sensitive to most antibacterial agents. Moreover, the acute oral toxicity test of LAB had no adverse effect on body weight gain, food utilization and organ indices in Kunming mice. In conclusion, the four LAB isolated from yak feces have considerable potential to prevent and/or treat yak bacterial disease-related diarrhea.